COMPOSITION WRITING ABILITY OF PRE-SERVICE SPECIAL EDUCATION STUDENTS: AN ANALYSIS - Rufo A. Labarrete (Universitas Negeri Padang, 2016)
Thestudy aimed to analyze the composition writing ability developed through the process approach following both free and controlled exercises formats of the 84 junior pre-service special education teachers of the Leyte Normal University for AY 2014-2015. It adopted the descriptive cross-sectional survey research design and had used Jacobs’ English as a Second Language Composition Profile as the instrument of the study. For valid and reliable interpretation of data, the mean and t - test were used. Results showed that the level of the respondents’ composition writing ability developed through free-exercises in terms of organization, vocabulary and language component were rated to be at “average good” level. In terms of content and mechanics; the respondents’ compositions were both rated “poor to fair” by the four raters. On the other hand, the level of the respondents’ composition writing ability developed through controlled-exercises in terms of content, organization, and language were at the average to good level while their vocabulary and mechanics components were rated poor to fair level. The over-all or general level of the respondents’ composition writing ability developed in both free and controlled exercises is at the average to good level. The raters noted that the respondents committed errors the most in mechanics, vocabulary and language use.